Assessing the Feasibility of Using a Multiplex Serological Assay to Conduct Serosurveillance for Malaria Exposure in Deployed Military Personnel - Sidhartha Chaudhury; Jessica S. Bolton; Edwin Kamau; Elke S. Bergmann-Leitner (Tropical Medicine and Infectious Disease)
Reproducibly assessing malaria exposure is critical for force health protection for military service members deployed to malaria-endemic regions as well as for civilians making public health decisions and evaluating malaria eradication efforts. However, malaria disease surveillance is challenged by under-reporting, natural immunity, and chemoprophylaxis, which can mask malaria exposure and lead to an underestimation of malaria prevalence. In this study, we determined the feasibility of using a serosurveillance-based approach to measure Anopheles vector exposure, Plasmodium sporozoite exposure, and blood-stage parasitemia using a multiplex serological panel. We tested post-deployment samples obtained from U.S. service members returning from regions with malaria risk to assess the potential of this serosurveillance panel. The results identified that some service members had anti-CSP antibody levels comparable to those found in endemic populations, suggesting exposure to sporozoites while those individuals were on chemoprophylaxis. We also observed isolated cases of anti-MSP1 levels that were as high as those observed in endemic populations and in CHMI studies, suggesting possible cases of clinical or subclinical parasitemia. The study demonstrated the feasibility of implementing a multiplex serology approach for conducting serosurveillance for Anopheles vector exposure and Plasmodium parasite exposure in samples collected following military deployments and its potential to support public health policies.